Differential regulation of polysaccharide-specific antibody responses to isolated polysaccharides, conjugate vaccines, and intact Gram-positive versus Gram-negative extracellular bacteria. Issue 30 (24th June 2016) - Snapper, Clifford M.
Highlights: Antibody responses to isolated polysaccharides are T cell-independent (TI). TI responses require both Ig crosslinking and second signals from innate immunity. IgG responses to polysaccharides on intact bacteria are T cell-dependent (TD). TD IgG responses to conjugate vaccines and bacteria differ mechanistically. TD IgG responses to Gram-positive versus Gram-negative bacteria show distinct features. Abstract: Bacterial capsular polysaccharides are major virulence factors and are key targets in a number of licensed anti-bacterial vaccines. Their major characteristics are their large molecular weight and expression of repeating antigenic epitopes that mediate multivalent B cell receptor cross-linking. In addition, since the majority of these antigens cannot associate with MHC-II they fail to recruit CD4+ T cell help and are referred to as T cell-independent antigens. In this review I will discuss a series of studies from my laboratory that have underscored the importance of understanding polysaccharide-specific antibody responses within the context in which the PS is expressed (i.e. in isolation, as a component of conjugate vaccines, and expressed naturally by intact bacteria). We have shown that multivalent B cell receptor crosslinking, as mediated by polysaccharides, uniquely determines the qualitative response of the B cell to subsequent stimuli, but by itself is insufficient to induce antibody secretion or class switching. For these latter events to occur, second signals must act in concert with primary signals derived from the B cell receptor. The co-expression of polysaccharide and protein within intact bacteria promotes recruitment of CD4+ T cell help for the associated PS-specific IgG response, in contrast to isolated polysaccharides. Further, the particulate nature of extracellular bacteria confers properties to the polysaccharide-specific IgG response that makes it distinct immunologically from soluble conjugate vaccines. Finally, the underlying biochemical and/or structural differences that distinguish Gram-positive and Gram-negative bacteria appear to play critical roles in differentially regulating the associated polysaccharide-specific IgG responses to these groups of pathogens. These studies have a number of implications for the understanding and future design of polysaccharide-based vaccines.